«Pipe in Pipe» Heat Pipeline as Alternative Variant of Two-Pipe Laying - B. A. Bairashevsky; N. P. Borushko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2006)
A method has been developed for calculation of final temperature while taking into account heat losses at the region of a heat exchanger to be designed in accordance with “pipe in pipe” principle. In addition to conventional scheme for two heat-exchanging flows the paper considers a heat-exchange case of three flows that are moving along ring channels relative to each other by П and Z schemes. The given calculative method has made the basis for the development and investigation of operational modes of the pipeline with one and two ring channels.Prospects of the technical solution of the developments to be planned have been confirmed by the results of the investigations and calculations that were carried out with the help of a special computer program